Development and implantation of a Thesaurus of Manufacturing Engineering terms - Martín-Sánchez, María Jesús; Sevilla-Hurtado, Lorenzo; Martín, F. (My University, 2015)
Present work shows the teaching-learning experience developed in the Department of Manufacturing Engineering of the University of Malaga. This experience is based on the need to generate a specific glossary of manufacturing engineering terms to be used as a study guide by the students. Eventually, it was decided to make a Thesaurus that would be aimed at a teaching activity. Also, it would take part in the educational innovation project PIE 13-025 of the University of Malaga, within the biennium 2013/2015. The first step consisted of the design of Thesaurus pattern, taking into account the kind of information that it was necessary include in it. Afterward, this pattern would be place on the Virtual Campus and the student would have to complete the information required. Finally, the results obtained in the different applications of this activity would be analyzed and evaluated.
Keywords: Ingeniería - Tesauros; Thesaurus; Technical terms; Manufacturing Engineering; Teaching